Seasonal strength performance and its relationship with training load on elite runners - Balsalobre-Fernandez, C.; Tejero-Gonzalez, C. M.; del Campo-Vecino, J. (Journal of Sports Science & Medicine, 2015)
The aim of this study was to analyze the time-course of force production of elite middle and long-distance runners throughout an entire season and at the end of the off-season, as well as its relationships with training load and hormonal responses. Train-ing load was recorded daily throughout an entire season by measuring and evaluating the session distance (km), training zone and session-RPE in a group of 15 elite middle and long-distance runners (12 men, 3 women; age = 26.3 ± 5.1yrs, BMI = 19.7 ± 1.1). Also, basal salivary-free cortisol levels were meas-ured weekly, and 50-metre sprints, mean propulsive velocity (MPV), mean propulsive power (MPP), repetition maximum (RM) and peak rate of force development (RFD) of half-squats were measured 4 times during the season, and once more after the off-season break. There were no significant variations in force production during the season or after the off-season break, except for the RFD (-30.2%, p = 0.005) values, which changed significantly from the beginning to the end of the season. Signif-icant correlations were found between session-RPE and MPV (r = -0.650, p = 0.004), MPP (r = -0.602, p = 0.009), RM (r = -0.650, p = 0.004), and the 50-metre sprint (r = 0.560, p = 0.015). Meanwhile, salivary-free cortisol correlated significantly with the 50-metre sprint (r = 0.737, p < 0.001) and the RM ( r = -0.514, p = 0.025). Finally, the training zone correlated with the 50-metre sprint (r = -0.463, p = 0.041). Session-RPE, training zone and salivary-free cortisol levels are related to force produc-tion in elite middle and long-distance runners. Monitoring these variables could be a useful tool in controlling the training pro-grams of elite athletes.